Menedzsment módszerek az Ipar 4.0 tükrében - Filep, Roland (International Journal of Engineering and Management Sciences, 2020)
The fourth industrial revolution poses major challenges for organisations in terms of technological aspects and from a management point of view, too. Good (effective) management is vital as it can help overcome the difficulties arising from shortages of skilled labour and from cost-cutting pressures, and it can help improve efficiency of resources. Innovations require management methods that support the introduction of industry 4.0. In my review of the literature, I aim to find out how the current level of sophistication in this new field can help managers of SME to better embrace change. Based on the reviewed literature, from management point of view, organisational structure, leadership style and HR practices are key to creating an atmosphere conducive to learning and innovation. In terms of structure, researchers do not suggest one thing to apply, but emphasise that industry 4.0 is characterised by an unstable, changing environment, so it is worth developing a structure that is characterised by decentralisation, few rules, horizontal communication and collaborative teamwork, i.e. much more organic than mechanical. In terms of different leadership styles, it is the transformational leadership that is the most often mentioned, however, in case of industry 4.0, we need even more because it can have various limitations. Even before industry 4.0, literature has highlighted that the recommended leadership style can be defined as the combination of transformational and transactional leadership; research in industry 4.0 in recent years also emphasises that it is the expanded construction of a knowledge-driven leadership style that blends the two, which can best facilitate innovation and learning. Managers can develop employee skills and improve their learning abilities through a variety of HR practices. So the right structure, leadership style and HR prepare the organisation for industry 4.0 by facilitating learning, improving skills and innovation.